Difficulty in Advancing Flexible Epidural Catheters When Establishing Labor Analgesia: An Observational Open-label Randomized Trial. Issue 1 (23rd March 2022) - Pancaro, C.; Purtell, J.; LaBuda, D.; Saager, L.; Klumpner, T.T.; Dubovoy, T.; Rajala, B.; Singh, S.; Cassidy, R.; Vahabzadeh, C.; Maxwell, S.; Manica, V.; et al.
Abstract : ( Anesth Analg . 2021;133:151–159. doi: 10.1213/ANE.0000000000005526) Flexible epidural catheters have a lower incidence of both paresthesias and intravascular catheter placement. This study aimed to compare and analyze the efficacy of 2 commercially available epidural kits: kit "A" (single-end hole wire-reinforced polyurethane epidural catheter; n=135) and kit "B" (multi-orifice wire-reinforced polyamide nylon blend epidural catheter; n=122).